(untitled) (American Journal of Islam and Society, 2010)
Books Reviewed: Valentine M. Moghadam, ed., From Patriarchy to Empowerment: Women’s Participation, Movements, and Rights in the Middle East, North Africa, and South Asia. Syracuse, NY: Syracuse University Press, 2007; Ida Lichter, Muslim Women Reformers: Inspiring Voices against Oppression. Amherst, NY: Prometheus Books, 2009; Wahida Shaffi, ed., Our Stories, Our Lives: Inspiring Muslim Women’s Voices. Bristol, UK: The Policy Press for the Joseph Rowntree Foundation, 2009. The realm of gender studies is rife with potential research foci: to comprise the geographical, political, and ethical breadth that spans North Africa to South Asia, war novels and Iranian cinema to dowries and hudud is, then, a veritable feat. Assuming the concept of patriarchy as the nexus from which to assess the multidimensional subjugation of women within the political, socioeconomic, and ethnic spheres, Valentine M. Moghadam affords a sweeping, yet insightful, collection of nineteen articles originating from the “Women in the Global Community” conference hosted in Istanbul by the Fulbright Commission in September 2002 ...